5x-2cosx-1=0

Simple and best practice solution for 5x-2cosx-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2cosx-1=0 equation:

Simplifying
5x + -2cosx + -1 = 0
Reorder the terms:
-1 + -2cosx + 5x = 0
Solving
-1 + -2cosx + 5x = 0
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + -2cosx + 1 + 5x = 0 + 1
Reorder the terms:
-1 + 1 + -2cosx + 5x = 0 + 1
Combine like terms: -1 + 1 = 0
0 + -2cosx + 5x = 0 + 1
-2cosx + 5x = 0 + 1
Combine like terms: 0 + 1 = 1
-2cosx + 5x = 1
Add '-5x' to each side of the equation.
-2cosx + 5x + -5x = 1 + -5x
Combine like terms: 5x + -5x = 0
-2cosx + 0 = 1 + -5x
-2cosx = 1 + -5x
Divide each side by '-2osx'.
c = -0.5o-1s-1x-1 + 2.5o-1s-1
Simplifying
c = -0.5o-1s-1x-1 + 2.5o-1s-1
Reorder the terms:
c = 2.5o-1s-1 + -0.5o-1s-1x-1

Related pages

lcm calculator for fractions3y 4x 12equations calculator with stepswhat is 30 percent of 2800what is the gcf of 60 and 72what is the square root of 1681prime factorization of 104220-45fractions adding calculatorcalculator for multiplying fractionscastlelearning com mobile2x 3y 5x 2 3x 3y 21.4375 as a fractionderivative of cosinedifferential of cos 2xsquare root of 2209simplify 8x 4xderivative of ln 1 x8y 9585.9multi step equation solverhcf of 72ln3 ln2cosexmx b calculatorcos4x cos2x1965 in roman numeralsgcf of 54 and 72prime factorization of 230factor 3x2-5x-2sin x derivat33-103133-50solving inequalities with fractionswhat is prime factorization of 635.8 as a decimalfraction and equation calculator5x 7y 35 solve for ythe prime factorization of 49prime factorization of 55how much is 4000 rupees in pounds9k11square root 75 simplified1234567890 qwertyuiop asdfghjkl zxcvbnmwhats a gcfln2-ln1what are factors of 2x2 9x 92y x yfactorization calculatorderivative of x cubedsimplify 3x 2xmml roman numeralscommon multiples of 20 and 25gcf of two monomials calculator91 roman numeralsfactoring x 3 x 2 x 1how to factor by gcfwhat is the prime factorization of 3104x2 4x 1least common denominator of fractions calculatorleast common factor finder32 qt to gal1 cosx derivativelcm math calculatortaxi tip calculatormath problems solver with steps4x 3y 9what is the lcm calculatorgcf monomials calculatormath problems solver with stepscommon multiples of 7x squared minus xadding mixed number fractions calculatorsinx cos xcos and coxxtanx7abc4squaredwww mhcitts comeazy mathdifferentiation of cos 3x